Organophosphites: an addition to the arsenal of organocatalysts - Baral, Nilofar; Rani, Soniya; Saikia, Pinku; Maity, Pradip (European Journal of Organic Chemistry, 2023)
Organophosphites are nucleophilic in nature and can act as a good leaving group owing to the stability of the phosphite anion. This dual reactivity makes them good candidates for nucleophilic organocatalysis. However, phosphites were introduced only in 2004 as the umpolung catalyst for acylsilane substrates utilizing sequential Brook rearrangements. Very recently, phosphites have been reported to catalyze aza-rearrangements and radical reactions. In this review, we discuss the reactivity parameters to understand its lack of use, as well as the potential for catalysis.
Keywords: acylradical; azaacyl equivalent; cylanion; organocatalysis; phosphite

N-SO3H functionalised brønsted acidic ionic liquid catalysed sequential one-pot synthesis of 2-amino-3-cyanopyridines via claisen-schmidt condensation under solvent-free condition - Das, Sukanya; Paul, Subham; Kashyap, Niharika; Saikia, Pinku; Borah, Ruli (Chemistryselect, 2024)
This work presents a simple approach for the synthesis of 2-amino-3-cyanopyridines via a one pot two-step sequential route catalysed by direct N–SO3H functionalised Br & oslash;nsted acidic ionic liquids (BAILs). Herein, catalytic activities of four BAILs namely ([TSPi][Cl](2), [DSIM][TFA], [EDSIM][TFA] and [DBDSA][TFA]) were explored and among them [TSPi][Cl](2) was found to be the most efficient reusable homogeneous catalyst. This process involves the ionic liquid catalysed in situ generation of chalcones from Claisen-Schmidt condensation between aromatic aldehydes and acetophenone/4-Cl acetophenone, followed by multicomponent reaction (MCR) with malononitrile and ammonium acetate using the same IL catalyst to selectively produce 2-amino-3-cyanopyridine derivatives in a solvent-free medium at 80 degrees C within 30-60 minutes in high yields (96-86 %). This amalgamation of MCR with ionic liquids and solvent-free conditions makes the present work more compliant with the protocols of Green Chemistry.
Keywords: 2-amino-3-cyanopyridines; Bronsted acidic ionic liquids; chalcones; Multicomponent reaction; One-pot approach

Unified photoredox-catalyzed aerobic oxidative dynamic kinetic asymmetric transformation for C-N atropoisomers mediated by chiral organophosphites - Saikia, Pinku; Aarthika, M.; Bhattacharjya, Ayantika; Maity, Susmita; Bajpai, Priyam; Bera, Asish; Saha, Arindam; Gonnade, Rajesh G.; Vanka, Kumar; Maity, Pradip (Organic Letters, 2025)
The synthesis of anilides with a chiral C(=O)-N axis has relied on direct installation of the chiral C(sp2)-N(sp2) bond or enantioselective modification of the peripheral groups. However, these methods are constrained by the size and type of functional groups compatible with each strategy. Herein, we report a dynamic kinetic asymmetric transformation (DYKAT) for the aerobic oxidation of iminium ions to access C(=O)-N axial chirality that addresses those limitations. Furthermore, it eliminates the need for any auxiliary functional groups, which enables us to develop a unified method for the synthesis of atroposelective isoquinolone, lactam, and amide.